On Household Wealth Trends in Sweden over the 1990s - N. Anders Klevmarken (Uppsala University, Department of Economics, 2003)
Influenced by a major tax reform in the beginning of the 1990s and by the exceptional boom in the stock market at the end of this decade the level as well as the inequality of the wealth of Swedish households have increased. The large baby-boom cohorts of the 1940s have been successful in accumulating wealth and they also have large claims on the public pension system. The implicit wealth in the form of these claims dominates private wealth in most Swedish households, and in this paper it is argued that private life-cycle savings have been small in Sweden. Most of these savings have been done though the public pension systems. However, concern about the future viability of the pension systems has probably increased private life-cycle savings in the 1990s.
urn:nbn:se:uu:diva-4497
Keywords: D31; 330; Distribution of wealth; tax reform; pension wealth; age-cohort effects; Vermögensverteilung; Steuerreform; Altersvorsorge; Bevölkerungsentwicklung; Schweden